Exploring Social Media Technologies Awareness and Use among Postgraduate Students of Library and Information Science in Nigeria: An Investigative Study - Nduka, Stella Chinnaya; Popoola, Sunday Olanrewaju (International Journal of Knowledge Content Development & Technology, 2024)
The prominent role accorded to social media in the academic community for research, teaching and learning revolves around its significance among users. Social media offers a platform for individuals to engage with and share perceptions relating to different disciplines. This current research was conducted to investigate the level of awareness and frequency of social media technology use among postgraduate students of Library and Information Science in Nigerian universities. The descriptive survey design was used for the study. Structured questionnaires were used to collect data from 919 library and information science (LIS) postgraduate students in the universities. In all, 742 copies out of the 919 distributed were returned and found usable, thereby making the return rate to be 81%. Data collected were analysed using mean and standard deviation. The study revealed that the LIS postgraduate students frequently use social media such as Wikipedia (x=3.94>3.50), Instagram (x=3.86>3.50), Facebook (x=3.85>3.50), Zoom (x̄=3.78>3.50), LinkedIn (x=3.69>3.50), YouTube (x̄=3.54>3.50), Twitter (x=3.52>3.50). The study established that students use social media tools for their personal, professional and research activities. The study also found that the level of awareness and use of social media by the students was high. The study recommended that the use of social media should be incorporated into the LIS curriculum including training sessions for the students on how to use the media effectively.